2006
DOI: 10.1021/jm0607193
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin and Dehydrozingerone Derivatives:  Synthesis, Radiolabeling, and Evaluation for β-Amyloid Plaque Imaging

Abstract: Alzheimer's disease (AD) is pathologically characterized by the accumulation of amyloid plaques and neurofibrillary tangles in the brain, and thus, the in vivo imaging of plaques and tangles would be beneficial for the early diagnosis of AD. It has been suggested that 5-hydroxy-1,7-bis(4-hydroxy-3-methoxyphenyl)-1,4,6-heptatrien-3-one (curcumin) may be responsible for low age-adjusted prevalence of AD in India. In the present study, eight novel derivatives of curcumin and 4-(4-hydroxy-3-methoxyphenyl)-3-buten-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
144
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(162 citation statements)
references
References 38 publications
15
144
2
1
Order By: Relevance
“…More recently, in a study examining the tissue distribution of radiolabeled fluoropropyl-substituted curcumin mice, Ryu et al found that curcumin bound to b-amyloid plaques in the brain, thereby suggesting its possible use for brain imaging (Fig. 2) [158].…”
Section: Q5mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, in a study examining the tissue distribution of radiolabeled fluoropropyl-substituted curcumin mice, Ryu et al found that curcumin bound to b-amyloid plaques in the brain, thereby suggesting its possible use for brain imaging (Fig. 2) [158].…”
Section: Q5mentioning
confidence: 99%
“…Data are expressed as the percent injected dose per gram of tissue (% ID/g). The data is replotted from [158].…”
Section: Q5mentioning
confidence: 99%
“…To visualize retinal Aβ pathology in vivo, we had previously developed a noninvasive retinal amyloid imaging method for rodent ADtg models, using curcumin as a contrast agent (40,51). Curcumin is a natural and safe phytopolylphenol fluorochrome that binds to Aβ fibrils and oligomers with high affinity and specificity (62)(63)(64)(65)(66)(67)(68). This approach enabled noninvasive detection and monitoring of individual retinal Aβ deposits in live ADtg mice (40,51).…”
Section: Introductionmentioning
confidence: 99%
“…Methods have been developed recently to increase the stability and increase the availability in vivo (Anand et al 2007). Curcumin derivatives can be used as a marker in PET scanning as suggested by Ryu et al (2006). Researchers at the Commonwealth Scientific and Industrial Research Organization in Australia used curcumin fluorescence imaging to highlight beta-amyloid in the retina and correlated them with the PET findings in the brain.…”
mentioning
confidence: 99%